The importance of being Earnest - Kitanovska-Kimovska, Sonja (Acta neophilologica, 2016)
Irony has significant stylistic function in texts. Given that in many cases it works in a certain linguistic, cultural, social and political context, irony may present a major challenge for the translator. The challenge involves not only recognizing and understanding it, but, perhaps, more importantly, conveying it in the target language so that all its stylistic effects become accessible for the target language reader. The purpose of this paper is to examine the strategies used to translate irony from English into Macedonian as well as to identify if there is any correlation between the type of irony and the translation strategy used. The results are based on an analysis of Oscar Wilde's The Importance of Being Earnest and its translation into Macedonian. The study focuses on ironic utterances and their rendition in translation. The method combines qualitative and quantitative approaches.
Keywords: angleška književnost; English literature; ironija; makedonščina; McCabe, Eugene, 1930-; prevajanje; strategies; strategije; translating irony; translation; Wilde, Oscar: The importance of being Earnest